Ferritin triggers neutrophil extracellular trap-mediated cytokine storm through Msr1 contributing to adult-onset Still’s disease pathogenesis - Jia, Jinchao; Wang, Mengyan; Meng, Jianfen; Ma, Yuning; Wang, Yang; Miao, Naijun; Teng, Jialin; Zhu, Dehao; Shi, Hui; Sun, Yue; Liu, Honglei; Cheng, Xiaobing; et al. (Nature communications, 2022)
Hyperferritinemic syndrome, an overwhelming inflammatory condition, is characterized by high ferritin levels, systemic inflammation and multi-organ dysfunction, but the pathogenic role of ferritin remains largely unknown. Here we show in an animal model that ferritin administration leads to systemic and hepatic inflammation characterized by excessive neutrophil leukocyte infiltration and neutrophil extracellular trap (NET) formation in the liver tissue. Ferritin-induced NET formation depends on the expression of peptidylarginine deiminase 4 and neutrophil elastase and on reactive oxygen species production. Mechanistically, ferritin exposure increases both overall and cell surface expression of Msr1 on neutrophil leukocytes, and also acts as ligand to Msr1 to trigger the NET formation pathway. Depletion of neutrophil leukocytes or ablation of Msr1 protect mice from tissue damage and the hyperinflammatory response, which further confirms the role of Msr1 as ferritin receptor. The relevance of the animal model is underscored by the observation that enhanced NET formation, increased Msr1 expression and signalling on neutrophil leukocytes are also characteristic to adult-onset Still’s disease (AOSD), a typical hyperferritinemic syndrome. Collectively, our findings demonstrate an essential role of ferritin in NET-mediated cytokine storm, and suggest that targeting NETs or Msr1 may benefit AOSD patients. Hyperferritinemic syndrome is a collective term for a group of severe inflammatory conditions distinguished by high ferritin levels, including adult-onset Still’s disease and COVID-19. Here authors show in an animal model that high ferritin levels are not just a sign of hyperinflammation but also a pathogenic factor that triggers neutrophil leukocyte activation and extracellular trap formation.